Simulator Sistem Monitoring dan Peringatan Dini Kebakaran Gedung Berbasis Web - Ahmad Faisal; Samuel H Tirtamihardja (Website, 2019)
The fire detection simulator with SMS and web features is equipped with break glass detection, simultaneous alarms, water flow detection on sprinklers (flow switches), fireman switches, reset alarms, flame sensor, gas/smoke sensor and temperature sensor. The simulator is also equipped with a sound alarm, visual alarm, pressurized fan, and fire damper. The system uses a SIM800L module to send fire data via SMS and the ESP8266 Wi-Fi module to access fire data in web server that will be displayed on the web and recorded every detected fire in the database. The system can display map using the navigation feature on Google maps. In order to detect fires remotely, this system must always be connected to the internet and cellular networks. The DS18B20 temperature sensor has 98.66 % accuracy compared to mercury thermometer, and the average time of SMS receiving is 9 seconds.Simulator peringatan dini kebakaran dengan fitur SMS dan web dilengkapi dengan pendeteksi kebakaran titik panggil manual (break glass), alarm serentak (general alarm), pendeteksi aliran air pada sprinkler (flow switch), fireman switch, reset alarm, sensor nyala api, sensor gas/asap dan sensor suhu. Simulator ini juga dilengkapi alarm bunyi, alarm visual, pressurized fan dan fire damper. Simulator ini menggunakan modul SMS SIM800L yang berfungsi untuk mengirim data kebakaran melalui SMS dan modul Wi-Fi ESP8266 yang berfungsi untuk mengakses data kebakaran ke web server yang akan ditampilkan di web dan dicatat di database. Sistem dapat menampilkan peta menggunakan fitur navigasi di Google Maps. Agar dapat mendeteksi kebakaran dari jarak jauh, simulator harus selalu terhubung ke internet dan jaringan seluler. Sensor suhu DS18B20 mempunyai akurasi sebesar 98,66% terhadap thermometer air raksa dan waktu rata-rata yang diperlukan sampai SMS diterima adalah selama 9 detik.